Pengaruh Efikasi Diri dan Adversity Quotient Terhadap Prestasi Akademik Mahasiswa Pendidikan Ekonomi FKIP UNS Angkatan 2019-2021 - Wandasari Dwi Mawarni; Khresna Bayu Sangka; Feri Setyowibowo (Universitas Negeri Surabaya, 2023)
The study aims to determine the effect of self-efficacy and adversity quotient on the academic achievement of economic education students at FKIP UNS batch 2019-2021. This study used a quantitative descriptive research method with 169 respondents as research subjects in economics education students from class 2019-2021. The sampling technique was carried out by proportionate stratified random sampling with the criteria of currently carrying out learing activities and obtaining a IPK score. Pearson’s product moment was used to test the instrument’s validity, while Cronbach’s alpha was used to test its reliability. Data were descriptively analyzed and tested using classical assumptions before being analyzed using multiple linear regression and the coefficient of determination. The findings showed that : First, there was a positive and significant effect of self-efficacy on academic achievement of Economics Education students of FKIP UNS batch 2019-2021. Second, indicated a positive influence and significant adversity quotient on the academic achievement of Economics Education students of FKIP UNS batch 2019-2021. Third, indicated a positive and significant influence on self-efficacy and adversity quotient academic achievement of Economics Education students of FKIP UNS batch 2019-2021.